ANALISIS STRATEGI GURU DALAM MENGAJAR SISWA SLOW LEARNER PADA PEMBELAJARAN IPAS DI SDN 1 GETASRABI - Abshor, Devy Aufia; Wibowo, Deki; Nugraha, Yoga Awalludin; Rafsanjani, Toni Ardi (STKIP Melawi, 2025)
Abstract: A teacher must try to improve the effectiveness of student learning. The purpose of the study was to analyze the teacher's learning strategies for slow learner students at SDN 01 Getasrabi, especially in the subjects of Natural and Social Sciences. The type of qualitative research is a case study approach. The data collection techniques are observation, interviews, and documentation. The data analysis technique uses the Miles and Huberman model. Based on the analysis of observation and interview data for class V teachers at SDN 01 Getasrabi, data was obtained that one class V elementary school student had learning problems. The student was not yet fluent in reading, had limited vocabulary so that he had difficulty communicating, and had low comprehension of the material presented by the teacher. The results of the study were that there were learning strategies for slow learner students for class teachers at SDN 01 Getasrabi, including learning preparation, classroom management, using interesting learning models, methods, and media, giving rewards and punishments, adding special lesson hours for slow learner students, providing motivation, cooperation with parents, making rules, and conducting learning evaluations.Keywords: Teacher Strategy, Slow Learner Students, Natural and Social SciencesAbstrak: Seorang guru harus berupaya meningkatkan keefektifan belajar siswa. Tujuan penelitian untuk menganalisis strategi pembelajaran guru kepada siswa slow learner di SDN 01 Getasrabi terutama di mata pelajaran Ilmu Pengetahuan Alam dan Sosial. Jenis penelitian kualitatif pendekatan studi kasus. Teknik pengumpulan datanya yaitu observasi/pengamatan, wawancara, dan dokumentasi. Teknik analisis data menggunakan model Miles and Huberman. Berdasarkan analisis terhadap data observasi dan wawancara guru kelas V SDN 01 Getasrabi, diperoleh data ada satu siswa kelas V SD mengalami masalah belajar. Siswa tersebut belum lancar membaca, terbatasnya kosakata sehingga kesulitan dalam berkomunikasi, dan daya tangkap menerima materi yang disampaikan guru rendah. Hasil penelitian yaitu terdapat strategi pembelajaran terhadap siswa slow learner untuk guru kelas SDN 01 Getasrabi, diantaranya persiapan pembelajaran, pengelolaan kelas, menggunakan model, metode, dan media pembelajaran menarik, pemberian reward dan punishment, menambah jam pelajaran khusus untuk siswa slow learner, pemberian motivasi, kerjasama wali murid, membuat tata aturan, dan mengadakan evaluasi pembelajaran.Kata Kunci: Strategi Guru, Siswa Slow Learner, Ilmu Pengetahuan Alam dan Sosial